Reimagining Education: A Youth-Centered Curriculum (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the challenges faced by today’s youth in a digital age, focusing on technological dependence, mental health issues, and academic pressures. It highlights the importance of integrating competencies across various subjects, especially Art, Design, Math, and Science, to foster creativity, critical thinking, and problem-solving skills. Learner-centered approaches such as project-based and inquiry-based learning are emphasized for their role in enhancing student engagement and deep understanding. The paper also discusses effective assessment methods and the significant role of technology in modern education, advocating for responsible use and digital literacy. The findings underscore the need for a holistic, youth-centered curriculum to better prepare students for future challenges.